Rancang Bangun Multi Platform Edugame untuk Sejarah Khulafaurrasyidin - Sari, Binar Kurnia (PROtek : Jurnal Ilmiah Teknik Elektro, 2016)
Todays, history of Islam at the Khulafaurrasyidin government period has been educated at fifth grade of Madrasah Ibtidayah Muhammadiyah (primary school). Like the other history lessons, the material of the historical backdrop of Khulafaurrasyidin comprised of numerous substance and still conveyed conventionally, so at some point makes the understudy feel exhausted. As a result of it, this exploration fate is to make the historical backdrop of Khulafaurrasyidin will be additionally fascinating and all the more simple to learn for the understudy, that is utilizing instructive game which can play on desktop and portable. This diversion instruction served on frame visual 2D which made by Construct 2 for gamet motor and utilizing SDLC (System Development Life Cycle) technique Waterfall show. This instructive diversion has been outlined gotten to be 4 fundamental part, that is Abu Bakar ash-Shiddiq, Umar bin Khaththab, Utsman bin Affan and Ali bin Abi Thalib. Each part will diversion play direction, game, material, and test. As per the author look into on 3 Islamic grade schools and 2 Islamic middle schools to the understudy who as of now learn or not learn yet the historical backdrop of Khulafaurrasyidin, as much as 89% of understudy concur if this amusement instruction makes the History of Khulafaurrasyidin be all the more fascinating and simple to learn.